Website Based Draft Application - Soegoto, Yudistira; Soeikromo, D; Rohman, H S; Setiadi, F A; Pambudi, L (International Journal of Research and Applied Technology (INJURATECH), 2024)
The development of product sales through the internet has spread in Indonesia, even well known. There are many conveniences in shopping such as various types of products and services offered. The website application designed is expected to help the business of food products in promoting its business. With the increasing use of smartphones, it can facilitate ordering food products through the website. This research used a quantitative method where data collection was taken from the study and took some internet references. This design uses a case diagram, and the programming language used PHP with Laravel framework and MySQL as a database. The design of this application creation will discuss several parts in the application, including the login view, the appearance of the main page of the application, the appearance of the order form, the payment view, and the appearance of feedback. Therefore, this analysis is expected to produce an online buying and selling website with various features that can help sell food products